Al Auzānu fī ‘Urūḍi Syi’ri al Nabawiyyati li al Imām al Bar’i (Dirāsatun Taḥlīliyyatun fī ‘ilmi al ‘Arūḍi) - Cakra Borti, Dwi Bima; M. Daud, Izzat (Al-Uslub: Journal of Arabic Linguistic and Literature, 2020)
Imam Al-Bur'i's An-Nabawiyyah poem consists of 43 verses, which contain anxiety, hope and strangeness in his heart as well as praise for the Prophet Muhammad. In this thesis discussion, the author discusses the wazan and bahar and the benefits found in the An-nabawiyyah poem by Imam Al-Bur'i The purpose of this discussion is to know the wazan 'arudh and bahar 'arudh and the benefits found in this Shia An-Nabawiyyah by Imam Al-Bur'i. This research uses a qualitative approach or library method that is a method of data collection with documentation methods through books, journals, and other literature related to this research with the aim of establishing a theory foundation. The data analysis used is a descriptive analysis that is an analysis technique used to analyze the data by describing the data that has been collected without any intention of making generalisasai from the results of the study.The results of this study show that the wazan and bahar arudh found in this An-Nabawiyyah poem are bahar Towil with wazan fa'ulun-mafa'iylun-fa'ulun-mafa'iylun 2x. and there are also some changes in wazan namely zihaf and illal in imam Bur'i's an-nabawiyyah poem.